2016
DOI: 10.3136/fstr.22.793
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Abrupt Increases in Postprandial Blood Glucose Levels by Rice Bread Made with the Novel Rice Cultivar “<i>Konayukinomai</i>”

Abstract: The amylopectin long-chain rice "Konayukinomai" (MAI) is high in resistant starch (RS). In this study, we confirmed that fine rice flour for bread making could be obtained using MAI, and compared the results to the highamylose cultivar "Koshinokaori" (KOR) and the conventional cultivar "Koshihikari" (HKR). MAI bread contained larger amounts of RS and slowly digestible starch (SDS) than that of HKR or KOR, and the RS content of MAI was easily changed by retrogradation and re-gelatinization of the starch. In a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…ALC rice cultivars were developed via chemical mutation (Satoh, 1994) or crossbreeding with ALC rice cultivars such as EM10 (Nishi et al, 2001) and Goami2 (GA2) (Choi et al, 2008), which have super-long chains (SLC) in amylopectin (Takahashi et al, 2001, Kubo et al, 2010. It is reported that rice flour bread made from the ALC rice cultivar Konayukinomai contains more RS and reduces postprandial blood glucose levels (Noro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…ALC rice cultivars were developed via chemical mutation (Satoh, 1994) or crossbreeding with ALC rice cultivars such as EM10 (Nishi et al, 2001) and Goami2 (GA2) (Choi et al, 2008), which have super-long chains (SLC) in amylopectin (Takahashi et al, 2001, Kubo et al, 2010. It is reported that rice flour bread made from the ALC rice cultivar Konayukinomai contains more RS and reduces postprandial blood glucose levels (Noro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some business operators are preparing to send notifications for lutein-rich spinach, and polyphenol-rich apple to CAA by utilizing the systematic reviews. rich satsuma mandarins [27][28][29][30], procyanidin rich apple [51], green tea rich in O-methylated catechin (epigallocatechin-3-O-(3-O-methyl) gallate (EGCG3′′Me)) [52], various other catechins [53], resistant starch rich rice [54], and zinc-rich oyster [55]. The most recent scientific findings obtained through this project are outlined below.…”
Section: Agricultural Products Registered In the Ffcmentioning
confidence: 99%